Fermentation of Glycerol from Biodiesel Waste to 1,3-Propanediol by Klebsiella Pneumoniae - Jekky Bahagia (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
One of the oldest products of glycerol fermentation is 1,3-Propanediol. As a glycol, 1,3-propanediol can principally be utilized as a monomer for the synthesis of polyesters and polyurethanes. In this study, 1,3-Propanediol is produced by fermentation of glycerol which is the result of purification of crude glycerol from biodiesel plants. Crude glycerol and glycerol of purification analyzed the content of compound. Glycerol is fermented by klebsiella pneumoniae. Glycerol is fermented with the addition of varying the volume of inoculum was 5, 7, and 10 % (v/v), the fermentation time was 1, 2 and 3 days, and the fermentation temperature was 25 and 37 oC. The results of fermentation of glycerol was analyzed using gas chromatography with column DB 5 HT to obtain a purity of 1,3-Propanediol is generated based on retention time of the standard solution. Retention time of 1,3-Propanediol is 4.846 minute on gas chromatographic analysis. The purity of 1,3-Propanediol at 1, 2 and 3 days is 59.444; 60.7145; and 73.7002 %. The purity of 1,3-Propanediol the addition of bacterial volume 5, 7, and 10 % (v/v) is 63.5320; 72.9740; and 73.7002 %. The purity of 1,3-Propanediol at 25 and 37 oC is 62.4343 and 73.7002 %.